2019
DOI: 10.1039/c9nj01211g
|View full text |Cite
|
Sign up to set email alerts
|

Applications of RAFT polymerization for chemical and enzymatic stabilization of l-asparaginase conjugates with well-defined poly(HPMA)

Abstract: HPMA RAFT polymerization and activation with variable linker chemistry for stabilization of l-asparaginase against pH, temperature, freeze–thaw and proteolytic stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…As shown in Figures 2C,D, a maximum immobilization efficiency of 68.4% was achieved after 2 h of cross-linking. In a similar study, ASNase was immobilized on poly[N-(2-hydroxypropyl) methacrylamide] in the same way, and 47.8% of the activity was retained, whereas the estimate for PEG-ASNase was reported to be 28.9% (Monajati et al, 2019). This result indicated that ASNase immobilization with NHS esters has the advantages of rapidity, high efficiency, and mild reaction conditions.…”
Section: Optimization Of Immobilization Conditionsmentioning
confidence: 85%
“…As shown in Figures 2C,D, a maximum immobilization efficiency of 68.4% was achieved after 2 h of cross-linking. In a similar study, ASNase was immobilized on poly[N-(2-hydroxypropyl) methacrylamide] in the same way, and 47.8% of the activity was retained, whereas the estimate for PEG-ASNase was reported to be 28.9% (Monajati et al, 2019). This result indicated that ASNase immobilization with NHS esters has the advantages of rapidity, high efficiency, and mild reaction conditions.…”
Section: Optimization Of Immobilization Conditionsmentioning
confidence: 85%
“…P(HPMA-MPEGA) was prepared via RAFT polymerization in methanol at 70 1C using 4,4 0 -azobis(4-cyanovaleric acid) (ACVA) initiator. 14 HPMA (100 mg), PEG acrylate (192 mg), CTA (1.4 mg) and ACVA (0.7 mg) were dissolved in methanol (2 mL). The solution was purged with N 2 for 30 min, sealed and incubated at 70 1C for 24 h. After polymerization, the polymer was purified by dialysis against deionized water for 72 hr and then freeze-dried.…”
Section: Synthesis Of P(hpma-mpega)mentioning
confidence: 99%
“…Recently, reversible addition-fragmentation chain transfer (RAFT) polymerization has allowed the development of monodisperse polymers with functional end-groups. 14 Herein, a random copolymer of HPMA and PEG acrylate P(HPMA-MPEGA) was synthesized via RAFT polymerization to prepare a novel biocompatible self-assembled nanogel with a-CD dimer (bisCD) through host-guest interaction. The stability and kinetics of pseudorotaxane complex formation were then examined when P(HPMA-MPEGA) was used instead of PEG alone.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in sharp contrast with PEG-Asp, P(CB-EG 3 Glu)-Asp elicits negligible antibodies without inducing ABC effect. In another example, Monajati et al [38] grafted poly N-(2-hydroxypropyl) methacrylamide (HPMA) to l-Asp. The Michaelis constant (K M ) and maximum velocity (V max ) values of poly(HPMA)-l-Asp (K M = 1.246 mm, V max = 32.72 µm min −1 mg −1 ) was similar to PEG-l-Asp (K M = 0.793 mm, V max = 33.92 µm min −1 mg −1 ), while exposure of PEG-l-Asp solution to six freeze-thaw cycles results in considerable loss of enzymatic activity (17%), which is comparable to full activity retention of poly(HPMA)-l-Asp, indicating poly(HPMA)-l-Asp has stronger freeze-thaw stability than PEG-l-Asp, and poly(HPMA) can serve as an effective alternative to PEG.…”
Section: "Grafting To" Polymerizationmentioning
confidence: 99%